The seeds multiply: the AcampaDOC International Documentary Film Festival - Vanhaelemeesch, Jasper (Universidad de Chile. Instituto de la Comunicación e Imagen, 2020)
Contemporary Central American film cultures can be conceptualised as postconflict, and post-Third-Worldist (Shohat, 2004), small (Hjort & Petrie, 2007) cinemas that, in absence of strong state-regulated support structures, have come to rely heavily on their relations to national and regional film festivals (Ahn, 2012). This paper introduces findings gained through ethnographic fieldwork at film festivals in the Central American and Spanish Caribbean regions, with a focus on the ACAMPADOC International Documentary Film Festival in Panama, the only film festival in the region dedicated exclusively to the documentary film genre. The paper also briefly refers to data from on-going research that maps Central American films and filmmakers in a basic network analysis. The reported findings broadly cover what are identified as five areas of concentration in the study of film festivals, based on the understanding of festivals as nodal interfaces for film cultures (Iordanova, 2015).